Modern Girls on the Go : Gender, Mobility and Labour in Japan. - Freedman, Alisa (Stanford University Press, 2013)
This spirited and engaging multidisciplinary volume pins its focus on the lived experiences and cultural depictions of women's mobility and labor in Japan. The theme of ""modern girls"" continues to offer a captivating window into the changes that women's roles have undergone during the course of the last century. Here we encounter Japanese women inhabiting the most modern of spaces, in newly created professions, moving upward and outward, claiming the public life as their own: shop girls, elevator girls, dance hall dancers, tour bus guides, airline stewardesses, international beau.